PENGARUH SIKAP SKEPTISME, PENGALAMAN AUDIT, KOMPETENSI, DAN INDEPENDENSI AUDITOR PADA KUALITAS AUDIT - Fortuna Sari, Ni Putu Piorina; Ramantha, I Wayan (E-Jurnal Akuntansi, 2015)
This research was conducted to determine the quality of the BPK audit Bali Provincial Legislative measured through attitude of skepticism, audit experience, competence and independence of an auditor. Audit quality is the ability of an auditor to obtain and evaluate audit evidence to find whether there is a discrepancy with the financial statement presentation standards. This research was conducted at the Supreme Audit Board of the Republic of Indonesia Bali Provincial Representative. The number of samples examined as many as 36 people auditor, with saturated sample method that can serve all the population sample. Data collected through questionnaires. The analysis technique used is multiple linear regression analysis. Based on the analysis concluded that the skepticism attitude, competence, and independence have positive effect and significant, while the audit experience has no effect on audit quality.
Keywords: attitude of skepticism, audit experience, competence, independence, audit quality.